The impact of leadership styles on the performance of workers in health organizations, An applied study in Asir Central Hospital during 2021 - Alshahrani, Nabil Ali Saeed (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the impact of leadership styles on the performance of workers, and therefore the study aimed to study the relationship between the three leadership styles (transformational leadership, transactional leadership, and servant leadership) on the performance of workers in Aseer Central Hospital during the year 2021. To achieve the objectives of the study, the researcher used The analytical descriptive approach, and the questionnaire for data collection, consist of two parts: the first section is general data, and the second section consists of four axes depending on the variables of the study. The study was applied to a sample of (305) hospital employees. It was extracted and analyzed on the SPSS statistical package program. One of the most important results of the study is that the three leadership styles affect the performance of employees to close degrees. It was also found that the reality of the managers' use of the leadership styles (transformational, mutual, and servant) is done to a high degree and to a close degree for each style, as it was found that the style of transformational leadership is the most used and influential style on the performance of employees with a correlation coefficient of (0.701). The fact that managers use the transactional leadership style is less used and comes in the third rank in terms of impact on the performance of employees with a correlation coefficient of (0.650). The effect of the servant leadership style is in the second rank in terms of the impact on the performance of employees with a correlation coefficient of (0.700). The study recommended the need for the hospital to choose its leadership with sufficient competence and experience by relying on several leadership styles and how to employ each style in the hospital. The study also recommended the need for managers to use the leadership style that suits their subordinates. departments in order to increase their leadership skills.
Keywords: leadership styles; employee performance; health organizations; Asir Hospital